Preferences of Users and Service Providers Towards the Road Transportation Network System that Supports Ports in Tanjungbalai City (Case Study: Teluk Nibung Port) - Richard Andeas Putra Marbun; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine the Preferences of Users and Service Providers Towards the Road Transportation Network System(Transportation Network System that Supports Ports in Tanjungbalai City (Case Study: Teluk Nibung Port). By using qualitative methods, this study is expected to provide an in-depth understanding of the preferences of users and service providers towards the Transportation Network System system that supports the Port of Teluk Nibung in Tanjungbalai, as well as explore the factors that affect their perception and needs. This chapter provides a methodological foundation for analyzing the data in the next chapter. The results of this study concluded that to increase the effectiveness of the road transportation network system (Transportation Network System) that supports the Port of Teluk Nibung, improvements in road infrastructure and better traffic management are needed. Through synergy between the government, logistics service providers, and port operators, it is hoped that this transportation system can function optimally, support the smooth operation of port activities, and increase the competitiveness of Teluk Nibung Port as the main port in the region.